2017
DOI: 10.1038/s41467-017-01273-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ice sheet melting driven by volcanic eruptions during the last deglaciation

Abstract: Volcanic eruptions can impact the mass balance of ice sheets through changes in climate and the radiative properties of the ice. Yet, empirical evidence highlighting the sensitivity of ancient ice sheets to volcanism is scarce. Here we present an exceptionally well-dated annual glacial varve chronology recording the melting history of the Fennoscandian Ice Sheet at the end of the last deglaciation (∼13,200–12,000 years ago). Our data indicate that abrupt ice melting events coincide with volcanogenic aerosol em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 72 publications
2
7
0
Order By: Relevance
“…Although direct evidence that a meltwater pulse occurred along this route immediately preceding the YD's onset is limited, some sediment core evidence suggesting that floods through the St Lawrence Valley coincided with the YD initiation does exist (Levac et al, 2015;Rayburn et al, 2011). A northward meltwater flow path along the MacKenzie Valley to the Arctic Ocean is also possible (Murton et al, 2010;Not and Hillaire-Marcel, 2012;Tarasov and Peltier, 2005). This is supported by both geological and modelling evidence, which suggests that a freshwater pulse into the Arctic Ocean could have weakened AMOC by > 30 %, considerably more that the < 15 % resulting from a similar pulse injected into the North Atlantic (Condron and Winsor, 2012).…”
Section: Compatibility With Other Hypothesessupporting
confidence: 62%
See 2 more Smart Citations
“…Although direct evidence that a meltwater pulse occurred along this route immediately preceding the YD's onset is limited, some sediment core evidence suggesting that floods through the St Lawrence Valley coincided with the YD initiation does exist (Levac et al, 2015;Rayburn et al, 2011). A northward meltwater flow path along the MacKenzie Valley to the Arctic Ocean is also possible (Murton et al, 2010;Not and Hillaire-Marcel, 2012;Tarasov and Peltier, 2005). This is supported by both geological and modelling evidence, which suggests that a freshwater pulse into the Arctic Ocean could have weakened AMOC by > 30 %, considerably more that the < 15 % resulting from a similar pulse injected into the North Atlantic (Condron and Winsor, 2012).…”
Section: Compatibility With Other Hypothesessupporting
confidence: 62%
“…Earlier research also briefly considered this spike based on absolute dating (Brauer et al, 1999b), but because of the concept that the LSE preceded the YD boundary by ∼ 200 years, concluded that an earlier sulfate spike most likely represented the LSE. Utilising the GICC05modelext chronology as well as recent layer counts within the MFM sediment (Lane et al, 2013a), we suggest that the sulfate spike at 12.867 ka BP represents the LSE, and that the earlier one tentatively identified by Brauer et al (1999b) may represent a small eruption of the Icelandic volcano Hekla, consistent with the interpretation of Muschitiello et al (2017). Although the coincidence between our identified sulfate spike, the date of the LSE, and the onset of North Atlantic cooling associated with the YD is compelling, detailed tephrochronological analyses are required to definitively ascribe this sulfate spike to the LSE.…”
Section: J U L Baldini Et Al: Evaluating the Link Between The Sulsupporting
confidence: 55%
See 1 more Smart Citation
“…We calculate the summer (JJA) surface energy and mass balance of DIC high-elevation area using the model described and calibrated for DIC by Morris and others (2014), a version of which has also been applied to palaeo ice masses (Muschitiello and others, 2017). Broadly, the model consists of four modules: surface energy balance; SMB; subsurface percolation and refreezing and vertical temperature flux, operating on a 1-D fixed vertical 1 cm grid.…”
Section: Methodsmentioning
confidence: 99%
“…Note that owing to the close proximity to the source region the local forcing would be exerted through both the radiative impacts of gas and particulate aerosols and the reduction in ice surface albedo produced by repeated extensive tephra deposition. With respect to the latter factor, recent estimations have shown the significance of volcanic ash deposition onto snow/ice even from mid-sized eruptions at high-latitudes to alter surface reflectivity and enhance glacier melting (e.g., Dadic et al, 2013;Young et al, 2014;Muschitiello et al, 2017). Given the continuous sustained explosive activity of the Antarctic volcanoes with related large production of tephra and consequent dispersal over the Plateau due to favourable atmospheric conditions (e.g., Scarchilli et al, 2011), we believe that the potential role of forcing caused by locally-derived ash deposits should not be neglected in Antarctic palaeoclimate reconstructions.…”
Section: Identification Of Tephra Sourcesmentioning
confidence: 99%